Solutions and services for smart sustainable district: an innovative approach in KPI to support transition. - Marilisa Cellurale; Carola Clemente; Paola Clerici Maestosi; Paolo Civiero (International Journal of Sustainable Energy Planning and Management, 2019)
Here it will be presented the results of the research “SCC solutions for Positive Energy Districts - RdS / PAR2018 / 041”, a collaborative project between Sapienza University of Rome - PDTA Dept. and ENEA Energy Technology Dept. – Sustainable Energy Network. The broader purpose of the research has been to design a set of strategies to facilitate built environment transition to optimized urban models such as Smart Energy District. The research consider as starting point the urban vision in SET-Plan on Action 3.2 "Smart Cities and Communities" which support planning, deployment and replication of 100 Positive Energy District by 2025, with the aim to promote innovative research on models, methodologies planning tools and technology solutions for the short-medium term implementation.